Comparing TPACK-Based E-LKPD and Conventional Instruction in Science: Impacts on Digital Literacy and Higher-Order Thinking Skills - Novi Ratna Dewi; Putri Ulyatun Niswah; Sukimin Sukimin; Kuntoro Adi Juwanda (Yayasan Keluarga Guru Mandiri, 2026)
This study examines the effectiveness of a TPACK-based Electronic Student Worksheet (E-LKPD) on the digital literacy and higher-order thinking skills (HOTS) of eighth-grade students in science learning. A quasi-experimental non-equivalent control group design was employed, involving an experimental class (n=27) that used the TPACK-based E-LKPD and a control class (n=27) that received conventional instruction using printed LKPD. Data were collected through validated digital literacy questionnaires, HOTS assessments, and student perception questionnaires. Mann-Whitney U tests indicated statistically significant differences in both digital literacy (p=0.014) and HOTS (p=0.004), favoring the experimental group, with moderate effect sizes (0.4390). Spearman's correlation showed a strong positive relationship between digital literacy and HOTS (? = 0.686; p 0.001; 95% CI [0.519; 0.801]). Partial Least Squares Structural Equation Modeling (PLS-SEM) indicated that students' positive perceptions of the TPACK E-LKPD predicted their digital literacy (?=0.635;p=0.004), which in turn was associated with higher HOTS scores (?=0.218; p=0.0216). These findings show that TPACK-based E-LKPD is effective not only in improving two key 21st-century skills simultaneously, but also in revealing a mechanism in which positive student perceptions support digital literacy development and, in turn, higher-order thinking. The study provides empirical evidence for using TPACK as a design framework for digital science worksheets to support digital literacy and higher-order thinking in secondary science education.